The natural history of subjective tinnitus in adults: a systematic review and meta-analysis of ‘no-intervention’ periods in controlled trials - Phillips, John; McFerran, Don; Hall, Deborah A.; Hoare, Derek J. (Wiley, 2018)
Objectives